REKAYASA MESIN PENCETAK BUTIR BERAS SIMULASI DARI MATERI TANAMAN HUTAN - Iyus Hendrawan; Sutrisno; Purwiyatno Hariyadi; Y.Aris Purwanto; Rokhani Hasbullah (Jurnal Penelitian Hasil Hutan, 2015)
Indonesia is rich of non-rice carbohydrate source including forest intercropping plants. Simulated Rice Grain (SRG) was made from non-rice carbohydrate sources which had close characteristic to the physicochemical properties of flour and Ciherang grain variety. This paper studies the machine design of Simulated Rice Grain (SRG) made of non-rice carbohydrate from forest intercropping plant. SRG forming machine design is approached through the design criteria, design analysis, functional design and manufacturing processes, while SRG forming machine was tested using mixed material made from 30% of arrowroot starch, 42% of beneng taro flour and 28% of sorghum. The specification of SRG forming machine is 6.8 × 2.2 × 5.06 mm for die space dimension, 1.9–2.3 for pressure ratio, 600 N for pressure force, 70° for angle of repose, 0–5000 microseconds for space time length, capacity of 900 grain per hour and 25–80 °C for die space temperature regulator. It resulted SRG with length of 7.1 mm, thickness of 2.8 mm, slightly rounded shape, grain firmness of 0.1–2 N, rice grain density of 620–770 kg/m³ and grain weight of weight grain 17.5–29 g per 1000 grains.